(untitled) (Al-Qamar, 2022)
This world is the place of striving and the hereafter is the place of reward or punishment, where the believers will be rewarded with Paradise and the disbelievers will be punished with Hell. So, the way of Allah with His slaves is to test them with calamities and tribulations, so that the believer may be known from the kaafir and so that the truthful may be distinguished from the liar۔ Allah has given human beings blessings like wealth, health, position, etc. in what manner he uses these blessings. On the Day of Resurrection, a person will be asked about his life and the blessings of Allah. Those who succeed in the exam will be put in heaven and those who fail will be put in hell. Also, when the people of Hell will be admitted to Hell, they will be brought face to face to add to their humiliation and to confess this fact and to argue with each other. Allah has also made it clear that the quarrel of the people of hell is a reality. While it is a clear thing that every defeated party quarrels with each other after their defeat and humiliation and blames each other for the defeat. And those who achieve success love each other. So, the people of heaven will be greeting each other, and the people of hell will be arguing with each other. Therefore, in this article, the mutual a conflict of criminals in the Day of Judgment has been commented in the light of Quran and Hadith. And their contemporary implementation has also been done so that we become obedient to Allah in the real sense.